Lateral shifting of the first metatarsal head in hallux valgus surgery: Effect on sesamoid reduction - (:unkn) unknown (AMER ORTHOPAEDIC FOOT & ANKLE SOC, INC, 2003)
Thirty feet with hallux vaigus (HV) having grade 2 and 3 sesamoid stations on AP radiographs were examined after Lindgren-Turan oblique distal metatarsal osteotomy with a minimum follow-up of 12 months. Adductor tendon release from the lateral sesamoid was not performed to determine the isolated effect of distal metatarsal osteotomy on metatarsosesamoidal reduction. Of the 30 feet, 20 (67%) had reduced and 10 (33%) unreduced sesamoids at the follow-up. Ultimately, distal metatarsal osteotomy (DMO) with lateral shifting of the first metatarsal head more than 7.2mm was found to reduce the sesamoids in the great majority of the cases (95% CI 7.243-9.757). Sesamoid release is redundant for metatarsosesamoidal reduction if sufficient lateral shift of the first metatarsal head over the sesamoids is accomplished.
Keywords: hallux valgus; sesamoid reduction; distal metatarsal osteotomy; sesamoid release; CHEVRON OSTEOTOMY; DISPLACEMENT OSTEOTOMY; RADIOGRAPHIC ANALYSIS; GREAT TOE; FEET